2010
DOI: 10.1074/mcp.m000020-mcp201
|View full text |Cite
|
Sign up to set email alerts
|

Stt7-dependent Phosphorylation during State Transitions in the Green Alga Chlamydomonas reinhardtii

Abstract: Photosynthetic organisms are able to adapt to changes in light conditions by balancing the light excitation energy between the light-harvesting systems of photosystem (PS) II and photosystem I to optimize the photosynthetic yield. A key component in this process, called state transitions, is the chloroplast protein kinase Stt7/STN7, which senses the redox state of the plastoquinone pool. Upon preferential excitation of photosystem II, this kinase is activated through the cytochrome b 6 f complex and required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 53 publications
11
101
0
Order By: Relevance
“…Comparison of the target phosphorylation sites of Stt7 revealed a consensus motif in which the phosphorylated Ser is flanked by basic amino acids [36]. This motif was used for a bioinformatics search for new potential substrates of Stt7.…”
Section: Role Of Stt7/stn7 Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the target phosphorylation sites of Stt7 revealed a consensus motif in which the phosphorylated Ser is flanked by basic amino acids [36]. This motif was used for a bioinformatics search for new potential substrates of Stt7.…”
Section: Role Of Stt7/stn7 Kinasementioning
confidence: 99%
“…This motif was used for a bioinformatics search for new potential substrates of Stt7. Interestingly, this search revealed several nucleus-encoded factors that are involved in post-transcriptional steps of chloroplast gene expression, including Raa3 (a protein involved in trans-splicing of the psaA RNA), Tab2 (required 36,41] for translation of the psaB mRNA) and Nac2 (involved in the stability/processing of the psbD RNA). These data raise the possibility that the Stt7/STN7 kinase has a wider role and is also involved in chloroplast gene expression, although the phosphorylation of these proteins needs to be confirmed by phosphoproteomics.…”
Section: Role Of Stt7/stn7 Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…We found that phosphorylation at Thr 537 and Thr 541 of State Transition Protein Kinase7 (STN7) was affected by stress. In Arabidopsis, STN7 functions in the phosphorylation of the light-harvesting system of PSII and for the state transition, a process that balances the light excitation energy between PSII and PSI and optimizes the photosynthetic yield upon changes in light quality and quantity (Lemeille et al, 2010). Changes in phosphorylation at the known C-terminal STN7 sites Thr 537, Thr 539, and Thr 541 were also detected, and previous studies reported that phosphorylation at the C terminus of STN7 kinase is required for its stability under state 2 conditions (Willig et al, 2011).…”
Section: Stress Responses In Photosynthesismentioning
confidence: 99%
“…No interdependence seems to exist between the STN kinases at protein levels [25]. Nevertheless, it has been proposed that the activity of STN8 may be regulated by STN7 in Arabidopsis, because in the green alga Chlamydomonas reinhardtii the activity of STN8 homologue Stl1 is regulated by its phosphorylation in an Stt7-dependent manner [27].…”
Section: Introductionmentioning
confidence: 99%